Improvement of Scientific Writing Ability Through Dyadic Essay Techniques - Syarifudin Yunus; Maguna Eliastuti (STBA LIA - Jakarta, 2020)
Students' scientific writing skills tend to be inadequate. Students find it difficult to express ideas and ideas in a scientific context. Observations made on Indonesian Language Education Students Semester VII of Indraprasta University PGRI showed symptoms of a lack of student scientific writing activity. Structured Dyadic Methods cooperative learning model basically can be applied by lecturers in scientific writing lectures. Structured Dyadic Methods (SDM) is a paired system, which emphasizes collaboration that enhances students' scientific writing skills. So the Dyadic Essay technique should be suspected to be able to improve students' scientific writing skills. After going through a series of research processes, the dyadic essay technique as one of the cooperative learning models that only involves two members in one group (in pairs) and using structured techniques is proven to be able to improve scientific writing skills based on facts and data so that it is more easily poured into works scientifically coherent and systematic. There is sufficient influence between the dyadic essay technique on the scientific writing ability of Semester VII students in the Indonesian Language Study Program, with a r coefficient of 0.655. Through dyadic essay techniques, students with high levels of creativity have better writing skills so that there is interaction between and creativity in learning to write science.